Transcriptome Analysis of Epithelial and Stromal Contributions to Mammogenesis in Three Week Prepartum Cows - Casey, Theresa; Dover, Heather; Liesman, James; DeVries, Lindsey; Kiupel, Matti; VandeHaar, Michael; Plaut, Karen (PLOS ONE, 2011)
Transcriptome analysis of bovine mammary development has provided insight into regulation of mammogenesis. However, previous studies primarily examined expression of epithelial and stromal tissues combined, and consequently did not account for tissue specific contribution to mammary development. Our objective was to identify differences in gene expression in epithelial and intralobular stromal compartments. Tissue was biopsied from non-lactating dairy cows 3 weeks prepartum, cut into explants and incubated for 2 hr with insulin and hydrocortisone. Epithelial and intralobular stromal tissues were isolated with laser capture microdissection. Global gene expression was measured with Bovine Affymetrix GeneChips, and data were preprocessed using RMA method. Moderated t-tests from gene-specific linear model analysis with cell type as a fixed effect showed more than 3,000 genes were differentially expressed between tissues (P<0.05; FDR<0.17). Analysis of epithelial and stromal transcriptomes using Database for Annotation, Visualization and Integrated Discovery (DAVID) and Ingenuity Pathways Analysis (IPA) showed that epithelial and stromal cells contributed distinct molecular signatures. Epithelial signatures were enriched with gene sets for protein synthesis, metabolism and secretion. Stromal signatures were enriched with genes that encoded molecules important to signaling, extracellular matrix composition and remodeling. Transcriptome differences also showed evidence for paracrine interactions between tissues in stimulation of IGF1 signaling pathway, stromal reaction, angiogenesis, neurogenesis, and immune response. Molecular signatures point to the dynamic role the stroma plays in prepartum mammogenesis and highlight the importance of examining the roles of cell types within the mammary gland when targeting therapies and studying mechanisms that affect milk production.